Camrelizumab plus rivoceranib versus sorafenib as first-line therapy for patients with unresectable hepatocellular carcinoma: a cost–utility analysis in China and the United States - Zhao, Qiuling; He, Yimin; Nian, Zilin; Huang, Yongjian; Huang, Ruyi; Lai, Lijun; Yang, Lin (Frontiers in Pharmacology, 2025)
ObjectiveCamrelizumab plus rivoceranib (camr-rivo) has been shown to significantly improve overall survival (OS) in patients with unresectable or advanced hepatocellular carcinoma (HCC) in the CARES-310 trial. However, the cost-utility of this treatment remains unclear. Therefore, this study evaluated the cost–utility of camr-rivo versus sorafenib as a first-line systemic therapy for patients with unresectable or advanced HCC from the perspectives of the Chinese healthcare system and the United States (US) payers.MethodsBased on the CARES-310 trial, a partitioned survival model was constructed to estimate economic costs and health outcomes over a 10-year lifetime horizon. Drug costs were obtained from the public database, Red Book, and relevant literature. Health utility values were derived from the literature. One-way and probabilistic sensitivity analyses were performed. The willingness-to-pay (WTP) threshold was 36,627.25/QALY in China and 150,000.00/QALY in the United States.ResultsCamr-rivo yielded an additional 0.34 quality-adjusted life years (QALY) compared to sorafenib for patients with unresectable or advanced HCC. The incremental costs in China and the United States were 4,762.10 and 92,700.49, respectively, and the incremental cost–utility ratios (ICURs) were 14,174.40/QALY and 272,852.59/QALY, respectively. Sensitivity analyses indicated that the cost of rivoceranib and camrelizumab had the greatest impact on the ICUR in China and the United States. Scenario analyses showed that a price reduction of approximately 30% for camrelizumab and rivoceranib could make camr-rivo a cost-utility option in the United States.ConclusionAt the set WTP threshold, camr-rivo is a cost–utility treatment strategy compared to sorafenib as a first-line therapy for patients with unresectable or advanced HCC in China but not in the United States.